ByzRev 01.2019.003: Alexandru Prelipcean, Romanos’ Renaissance.: From the beginning to the present. Bibliography about Romanos the Melodist - Grünbart, Michael (The Byzantine Review, 2019)
Alexandru Prelipcean, Romanos' Renaissance. From the beginning to the present. Bibliography about Romanos the Melodos (Studien zur Orientalischen Kirchengeschichte 61). Berlin: LIT 2019. 80 S. – ISBN 978-3-643-91132-2 (29.90 EUR, 29.90 CHF)